The mechanical properties of tungsten grown by chemical vapour deposition - Murphy, J; Giannattasio, A; Yao, Z; Hetherington, C; Nellist, P; Roberts, S (Elsevier, 2009)
The mechanical properties of polycrystalline tungsten grown by chemical vapour deposition (CVD) have been investigated. Fracture tests were performed on the material over the 24-967 °C temperature range at a low strain rate. The material was found to be brittle or semi-brittle across the entire temperature range investigated. This behaviour differs significantly from that previously found in conventionally-grown polycrystalline tungsten, which, under similar experimental conditions, is found to be ductile above approximately 120 °C. Energy dispersive X-ray analysis indicates that in the CVD tungsten, there is a significant concentration of fluorine at grain boundaries. It is therefore suggested that fluorine segregation to grain boundaries is responsible for the increased brittleness observed in the CVD tungsten.